Rock magnetism and its application to palaeosols: A pilot study in a loess-palaeosol sequence of the Chacopam-Dean region - Vasquez, C.A. (1998)
Rock maenetism techniques were applied to the study of the palaeosols and loess in the Chaco-Pampean plain region, Buenos Aires, Argentina; in addition, several types of non magnetic analysis were carried out: chemical analysis of ferrous and ferric, titanium and magnesium ions and x-Ray difraction. The magnetic susceptibilities of the Argentine palaeosol and loess exhibit different trends to those observed in the well known Chinese examples with which they are compared. In the Chacopampean succession the susceptibility of the loess is higher than that of the palaeosol. This can be explained by differences in the parental material imparting different magnetic properties. © 1998 Asociaciön Geolögica Argentina.